Fault Diagnostics in PEMFC Stacks by Evaluation of Local Performance and Cell Impedance Analysis. Issue 4 (9th March 2020) - Mitzel, J.; Sanchez‐Monreal, J.; Garcia‐Sanchez, D.; Gazdzicki, P.; Schulze, M.; Häußler, F.; Hunger, J.; Schlumberger, G.; Janicka, E.; Mielniczek, M.; Gawel, L.
Abstract: Starvation, flooding, and dry‐out phenomena occur in polymer electrolyte membrane fuel cells (PEMFCs), due to heterogeneous local conditions, material inhomogeneity, and uneven flow distribution across the single cell active area and in between the individual cells. The impact of the load level and air feed conditions on the performance was identified for individual single cells within a 10‐cell stack. Analysis of the current density distribution across the active area at the cell level was correlated with electrochemical impedance spectroscopy to enable operando fault diagnostic without any impact of the applied analytical tools on the single cell behavior. Moreover, the combination of both technologies allows in‐depth analysis of fault mechanisms in fuel cell single cells with improved sensitivity. Current density distribution and the quantitative assessment of the performance homogeneity demonstrated high sensitivity to small humidity changes and allow the detection of critical events, such as dry‐out in single cells. Impedance analysis is more sensitive regarding polarization and diffusion limitations and allows detection of cell flooding. The combination of both techniques is required for reliable identification of air starvation faults.